2014
DOI: 10.1002/ejsp.2048
|View full text |Cite
|
Sign up to set email alerts
|

The inner speech of behavioral regulation: Intentions and task performance strengthen when you talk to yourself as a You

Abstract: People often talk to themselves using the first-person pronoun (I), but they also talk to themselves as if they are speaking to someone else, using the second-person pronoun (You). Yet, the relative behavioral control achieved by I and You self-talk remains unknown. The current research was designed to examine the potential behavioral advantage of using You in self-talk and the role of attitudes in this process. Three experiments compared the effects of I and You self-talk on problem solving performance and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 35 publications
(38 reference statements)
2
28
1
3
Order By: Relevance
“…Patrick and Hagtvedt (2012) compared the effects of refusal strategies involving "I don't" and "I can't" and found that the use of "I don't" resulted in relatively more positive behavior change than "I can't. " Zell, Warriner, and Albarracín (2012) and Dolcos and Albarracin (2014) noted that when individuals are performing tasks, they sometimes refer to themselves as "I" and other times as "you" and as "we." They found that participants who referred to themselves as if they were another person using "you" or "we" in circumstances that required behavioral regulation and conscious self-guidance performed better than participants who referred to themselves in the first person.…”
Section: Self-talkmentioning
confidence: 99%
“…Patrick and Hagtvedt (2012) compared the effects of refusal strategies involving "I don't" and "I can't" and found that the use of "I don't" resulted in relatively more positive behavior change than "I can't. " Zell, Warriner, and Albarracín (2012) and Dolcos and Albarracin (2014) noted that when individuals are performing tasks, they sometimes refer to themselves as "I" and other times as "you" and as "we." They found that participants who referred to themselves as if they were another person using "you" or "we" in circumstances that required behavioral regulation and conscious self-guidance performed better than participants who referred to themselves in the first person.…”
Section: Self-talkmentioning
confidence: 99%
“…A negative correlation between first-person singular pronouns (i) and second-person singular pronouns (you) is prominent in the anxiety sample, which appears to be most driven by texts with high I use and low you use. Considering that approaching personal challenges from a first-person rather than secondperson perspective tends to be associated with increased psychological distress, the pronoun usage of people posting in anxiety forums could represent a ruminative or otherwise suboptimal method of seeking and providing support (Dolcos and Albarracin, 2014;Kross and Ayduk, 2011).…”
Section: Out-of-sample Predictionsmentioning
confidence: 99%
“…We capitalised on this opportunity by examining whether third-person self-talk, a simple linguistic technique that promotes emotion regulation (e.g. Dolcos & Albarracin, 2014;Kross et al, 2014;Moser et al, 2017;Nook, Schleider, & Somerville, 2017;Streamer, Seery, Kondrack, Lamarche, & Saltsman, 2017;Zell, Warriner, & Albarracin, 2012), could "nudge" people living in the United States into reasoning about Ebola more rationally as concerns about this issue swelled. than about one's own.…”
Section: Introductionmentioning
confidence: 99%